Multidisciplinary Pain Management: A Tale of Two Outcomes. (13th January 2023) - Butler, Stephen H.; Loeser, John D.
Abstract : Economic implications of pain management . By Loeser JD. Acta Anaesthesiol Scand 1999; 43:957–95. Reprinted with permission. Multidisciplinary pain management was an invention of John J. Bonica, M.D. He started the Multidisciplinary Pain Clinic at the University of Washington in 1960. This clinical service evolved over the years, and when John Loeser, M.D., became its director in 1982, he collaborated with Bill Fordyce, Ph.D., to create what was known as "the structured program." The program has served as the model for pain treatment programs throughout the world, many of which have fared better than that at the University of Washington. The migration of Stephen Butler, M.D., to Uppsala, Sweden, in 2000 has given us the opportunity to contrast multidisciplinary pain management in the Nordic countries with that in the United States.